Xi hõnhã? e agora? vamos ser pesquisadores: um fazer pesquisa tikmũ’ũn entre múltiplos seres, saberes e fazeres - Paula Cristina Pereira Silva (2022)
This thesis is a concrete experience of doing research with the Tikmũ’ũn, also known as Maxakali, among multiple beings, types of knowledge, and practices. Its general objective was to understand a tikmũ’ũn way of doing research and its relationship with ‘doing school’. In this sense, this collectively produced research highlights the urgency of decolonizing research, to give visibility and recognition to the beings, knowledge, and actions of different peoples who, for centuries, were disregarded by the dominant Western society. The research participants are several beings, humans and also those considered ‘non-human’, who live in the Maxakali Territory of Água Boa, in the city of Santa Helena de Minas, Minas Gerais, Brazil. Tikmũ’ũn researchers and non-indigenous researchers produced the empirical material. Together they created the Hãm Yĩkopit Research Network (Ask the Earth) that shares research on different themes. These studies were developed, in person, by all the participants of the Network, in their respective villages, shared with each other through meetings of collective guidance. Due to the Covid-19 pandemic, the research material of this thesis also includes the remote production of a booklet with the results of the research carried out by the Network. Seeking to honor the authorship and protagonism of the Tikmũ’ũn, we seek a theoretical-methodological path that, in fact, dialogues with the cosmovision of these people. For this, we built guidelines for the analysis of research material based on tikmũ’ũn beings, knowledge, and doings, outlined by researchers in their studies. Following these guidelines, we refer to other studies on indigenous research methodologies based on the indigenous ancestral practice of storytelling (storytelling), also common among the Tikmũ’ũn, and that highlight the power of stories to teach (storywork), in order to value orality and focus on what the Network researchers wanted to tell us. We made alternate movements of analysis, sometimes positioning the analytical lenses on the macro, encompassing all the Network's research, while other times focusing on the micro, gathering the activities of one research of the Network's, connected to school practices in a specific village. The first analytical movement showed that several aspects learned, related to being- knowing-living tikmũ’ũn, and guided the way of doing research in the Network. The microanalysis made it possible to understand how such aspects guide the way of ‘doing tikmũ’ũn school’, which was connected with ‘doing research’. From the alternating movements of distance (macro) and approach (micro) to analyze the Network's research conducted as a whole and individually, we could see that tikmũ’ũn researchers move autonomously, seeking to transform the colonial heritage of territorial devastation, aiming to bring back the forest/woods and perceiving in research a way to do so. As a result, we can say that ‘doing research’ on the Network has simultaneously revealed the theoretical- methodological framework of the present research, based on the aspects of being-knowing-living tikmũ’ũn, as well as the strong connection between ‘doing research’ and ‘doing school’ that develops through a continual entanglement with Mother Earth. The creation of the Research Network strengthens and gives visibility to this way of research and to tikmũ’ũn school, highlighting the pedagogical and political power of this initiative. From this perspective, the Hãm Yĩkopit Research Network (Ask the Earth) is aligned with a research practice that is politically positioned, that advocates for social and cognitive justice through the production of knowledge that seeks to transform, from the micro, the reality of operative injustices.